The Association of Peripheral Blood Regulatory T-Cell Concentrations With Epithelial Ovarian Cancer: A Brief Report. Issue 1 (January 2017) - Cannioto, Rikki A.; Sucheston-Campbell, Lara E.; Hampras, Shalaka; Goode, Ellen L.; Knutson, Keith; Ness, Roberta; Modugno, Francesmary; Wallace, Paul K.; Szender, J. Brian; Mayor, Paul; Hong, Chi-Chen; Joseph, Janine M.; et al.
Abstract : Objective: There is a mounting body of evidence demonstrating higher percentages of regulatory T (Treg) cells in the peripheral blood of patients with cancer in comparison to healthy controls, but there is a paucity of epidemiological literature characterizing circulating Treg cells among patients with epithelial ovarian cancer (EOC). To investigate the role of peripheral Treg cells in ovarian neoplasms, we conducted a case–control study to characterize circulating concentrations of Treg cells among patients with EOC, women with benign ovarian conditions, and healthy controls without a history of cancer. Materials and Methods: Participants were identified for inclusion due to their participation in the Data Bank and BioRepository program at Roswell Park Cancer Institute in Buffalo, NY. Patients included 71 women with a primary diagnosis of EOC and 195 women with a diagnosis of benign ovarian conditions. Controls included 101 age- and race-matched women without a history of cancer. Nonfasting, pretreatment peripheral blood levels of CD3+CD4+CD25+FOXP3+ Treg cells were measured using flow cytometric analyses and expressed as a percentage of total CD3+ cells and as a percentage of total CD3+CD4+ cells. Results: Compared to healthy controls and women with benign ovarian conditions, patients with EOC had significantly higher frequency of Treg cells ( P < 0.04). In multivariable logistic regression analyses using Treg frequency expressed as a percentage of CD+3 cells, we observed a significant positive association between Treg cell percentage and EOC risk, with each 1% increase associated with a 37% increased risk of EOC (odds ratio, 1.37; 95% confidence interval, 1.04–1.80). We observed a similar trend when Treg frequency was expressed as a percentage of CD3+CD+4 cells (odds ratio, 1.22; 95% confidence interval, 0.99–1.49). Conclusions: The current study provides support that peripheral Treg cell frequency is elevated in patients with EOC in comparison to women with benign ovarian conditions and healthy controls.